InSAR coseismic deformation field and seismogenic structure of the 2020 Mw6.0 Jiashi earthquake and the implication for the moderate-magnitude seismicity in the southwestern Tian Shan, western China - Wu, Danruo; Chen, Zhidan; Zimin, Mikhail (Frontiers in Earth Science, 2024)
The Kepingtage fold-and-thrust belt in the southwestern Tian Shan hosts the 2020 Mw 6.0 Jiashi earthquake with no apparent surface ruptures. The thrust nappe structure in this region is characterized by moderate-magnitude (Mw5.5-6.5) seismic events, but the seismogenic mechanisms and controlling factors remain under investigation. In this study, we utilized Sentinel-1A SAR satellite data to reconstruct the InSAR coseismic deformation field of the 2020 Jiashi earthquake. To address the limitation imposed by residual orbital phases during the interferometric measurement, this paper proposed an automatic method that combines ascending and descending track data with terrain features for orbit refinement. Subsequently, we employed the jointly constrained deformation field after orbit correction to invert fault geometric parameters and fault slip distribution. Our results show that the 2020 Jiashi earthquake is characterized by vertical deformation with horizontal right-lateral component. The smooth interference fringes indicate continuous surface uplift and subsidence without detectable coseismic surface ruptures. The maximum uplift reaches up to ~0.08 m and the maximum subsidence is about 0.03 m. This event is best fitted by a north-dipping fault plane with a depth of 4.2 km, a dip angle of 11.6°, and a strike of 276° beneath the Keping thrust fault, roughly consistent with the previous studies. Combined with the published geological studies and seismic reflection surveys, we suggest that the seismogenic structure of the 2020 Jiashi earthquake is the lower ramp of the Keping thrust fault at the southwestern front of Tian Shan. The abrupt fault bend between the lower ramp and the upper ramp of the Keping thrust may limit the propagation of the coseismic rupture to the surface, thereby constraining the moment magnitude of the seismic event. The 2020 Jiashi event indicates that the discontinuities or irregularities of fault geometry along strike and dip and the weaker rock strength of the sedimentary cover above the detachment coherently define the moderate-magnitude seismicity in the southwestern Tian Shan region.